FGFR4 p.Gly388Arg polymorphism in PBMCs of LAM patients: findings of a pilot study - Koc-Gunel, Sinem; Ryan, Amy L.; Winter, Melanie; Wagner, Thomas O. F. (Frontiers in Medicine, 2025)
Lymphangioleiomyomatosis (LAM) is a rare, progressive lung disease characterized by neoplastic-like proliferation of abnormal smooth muscle–like cells, primarily driven by mutations in the TSC2 gene. These mutations result in hyperactivation of the mTOR signaling pathway, leading to uncontrolled cell growth. However, additional genetic variants may modulate disease progression and severity. In this observational pilot study, we investigated the potential role of co-occurring variants. Peripheral blood mononuclear cells from seven sporadic LAM patients were analyzed using next-generation sequencing to identify potentially tumorigenic variants. The FGFR4 p.Gly388Arg gain-of-function polymorphism was identified in four patients, with allelic frequencies ranging from 49 to 99%. Patients with the variant exhibited significantly faster rates of lung function decline, as measured by FEV₁%, compared to those without the variant. Spatial transcriptomic analysis of LAM lung tissue revealed FGFR4 expression predominantly in alveolar fibroblasts and AT2 epithelial cells, key compartments in lung remodeling, while detection in PBMCs supports a potential systemic role. These preliminary findings support the hypothesis that FGFR4 mutations contribute to the systemic aspects of LAM, potentially exacerbating disease severity. They also highlight the need for larger, mechanistic studies to evaluate FGFR4 as a biomarker or therapeutic target. Overall, this study provides a hypothesis-generating framework for future investigations into the genetic drivers of LAM beyond TSC2 mutations.